Futures markets, cognitive ability, and mispricing in experimental asset markets - Noussair, Charles; Tucker, Steven; Xu, Yilong (Journal of economic behavior & organization, 2016)
We study the effect of a futures market, in which contracts maturing in the last period of the life of the asset can be traded. Our experiment has two treatments, one in which a spot market operates on its own, and a second treatment, in which a spot and a futures market are active simultaneously. Futures markets lower spot prices, but increase price volatility. The futures markets themselves exhibit considerable overpricing. Individuals with higher cognitive reflection test (CRT) scores achieve greater earnings, and tend to sell in the overpriced futures market, while traders with lower CRT scores make purchases in the futures market. Greater average CRT score among a group of traders is associated with better price discovery when no futures market is present but there is no such relationship in the presence of a futures market. Modified measures of CRT, which take into account different types of incorrect responses, are introduced.
Gesehen am 10.05.2019